1995
DOI: 10.1007/bf00179394
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and DNA sequence of the b6w2 allotype of the rabbit immunoglobulin kappa 1 light chain (b locus)

Abstract: The b6w2 allotype of the constant region of the rabbit immunoglobulin kappa 1 (K1) light chain (b locus) was discovered in wild populations from northern Spain. At the serological level, the b6w2 allotype is characterized by the presentation of all b6-specific epitopes, while an allotypic determinant which is shared between the nominal b5 and b6 allotypes is lacking. The DNA fragment encoding the b6w2 allotype was amplified by means of the polymerase chain reaction, and sequenced directly by dideoxy-DNAsequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Genotypes were inferred from the phenotypic arrays (Table 1; cf. van der Loo et al 1991Loo et al ,1995Loo et al ,1998. Sera with phenotypes that could not readily be resolved into their putative allelic components were subjected to double gel immunodiffusion (Kelus and Steinberg 1991), a technique which allows one to verify whether determinants recognized by two different antibodies are epitopes of the same or of different molecular species in the test serum.…”
Section: Igkc1 Typingmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotypes were inferred from the phenotypic arrays (Table 1; cf. van der Loo et al 1991Loo et al ,1995Loo et al ,1998. Sera with phenotypes that could not readily be resolved into their putative allelic components were subjected to double gel immunodiffusion (Kelus and Steinberg 1991), a technique which allows one to verify whether determinants recognized by two different antibodies are epitopes of the same or of different molecular species in the test serum.…”
Section: Igkc1 Typingmentioning
confidence: 99%
“…The b6 allotype occurs in areas of type A as well as in areas of type B prevalence, often together with the b6w2 allotype. DNA sequence comparisons have shown that the b6w2 gene derives from the b6 gene lineage (van der Loo et al 1995). The b6 lineage is also present in RAD, implying the coalescence of the b6 genes of the major mtDNA lineages.…”
Section: Relevance To Igkc1-locus Evolutionary Patternsmentioning
confidence: 99%
See 1 more Smart Citation